2008
DOI: 10.15288/jsad.2008.69.906
|View full text |Cite
|
Sign up to set email alerts
|

The Social Network and Alcohol Use

Abstract: ABSTRACT. Objective: Previous research has found that a drinkingsupportive social network has a strong infl uence on heavy drinking and alcohol-related problems over time. The objective of this work was to understand the individual difference and interpersonal factors that predict changes in the social network relevant to alcohol use. Method: Data are from a large, ongoing prospective sample of 634 newly married couples in the United States. The current study examined the association between individual, relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
57
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 31 publications
6
57
0
Order By: Relevance
“…Some social network research has focused on how the alcohol drinkers in one's network infl uence individual drinking behaviors. Among both men and women, larger social networks of heavy drinkers are associated with a greater frequency of individual HED (Homish and Leonard, 2008;Manuel et al, 2007). Similarly, Wenzel et al (2009) found that the odds of HED were greater for homeless women who had a larger proportion of heavy drinkers in their social network.…”
Section: H Eavy Episodic Drinking (Hed) Frequency In the Unitedmentioning
confidence: 97%
“…Some social network research has focused on how the alcohol drinkers in one's network infl uence individual drinking behaviors. Among both men and women, larger social networks of heavy drinkers are associated with a greater frequency of individual HED (Homish and Leonard, 2008;Manuel et al, 2007). Similarly, Wenzel et al (2009) found that the odds of HED were greater for homeless women who had a larger proportion of heavy drinkers in their social network.…”
Section: H Eavy Episodic Drinking (Hed) Frequency In the Unitedmentioning
confidence: 97%
“…While the same is true of other populations, especially among the relatively young, the cultural norms for drinking and drug-taking among gay men, and the social context within which men socialise all contribute to the extensive use of alcohol and drugs 27. This structural or environmental proximity to alcohol and illicit drugs is exacerbated by positive norms for drinking and drug-taking—with respect to alcohol in particular, research supports the role of peers and partners in shaping individual patterns of use,28 and there is a strong correlation between drinking habits and perceptions of peer drinking habits among young people generally 29…”
Section: Motivations For Substance Usementioning
confidence: 99%
“…In a 10-year followup of middle-age adults, spouses of remitted problem drinkers achieved normal functioning and life contexts, whereas spouses of relapsed problem drinkers continued to experience some defi cits (Moos et al, 1990). With respect to predictors of spouse functioning, friends' and social network members' approval of, and engagement in, drinking is associated with more alcohol consumption among young and middle-age adults (Bullers et al, 2001;Caudill and Kong, 2001;Homish and Leonard, 2008;Leonard et al, 2000), as well as among older adults (Akers et al, 1989;Moos et al, 2004).…”
Section: Normalization and Predictors Of Spouse Functioningmentioning
confidence: 99%